An application of TOPSIS method for ranking different strategic planning methodology - Mohsen Esfandiari; Mehdi Rizvandi (Management Science Letters)
Strategic planning is one of the most popular methods for setting up long-term objectives, which normally deals with various criteria. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is a multi-criteria decision analysis method for ranking different alternatives based on various criteria. The method has been widely used among practitioners in different industries. This paper presents an empirical investigation to rank different business development strategies for information technology improvement. The study considers five different strategies including Critical Success Factors Analysis, Business Systems Planning, Porter's forces model, SWOT analysis, Value chain Analysis and MIN and rank them based on TOPSIS technique. The results of the implementation of TOPSIS has indicated that MIN method is ranked first as the most important factor followed by Business Systems Planning, Porter's forces model, Value chain Analysis, SWOT and CSF for development of strategic planning for information technology in municipality organization.